Exploiting relevance, novelty and diversity in tag recommendation - Belém, Fabiano; Martins, Eder; Almeida, Jussara; Gonçalves, Marcos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Tag recommendation methods have mostly focused on maximizing relevance, but other aspects may be as important for recommendation usefulness. We here define novelty and diversity for tag recommendation, and propose two new recommendation strategies that consider these aspects jointly with relevance. We evaluate the proposed strategies using real datasets from 3 popular Web 2.0 applications, achieving gains over the state-of-the-art of up to 21% in relevance, 45% in novelty and 2.5% in diversity.